Two Concepts of Wrongful Harm: A Conceptual Map for the Warsaw International Mechanism for Loss and Damage*. Issue 2 (4th May 2017) - Boran, Idil
Abstract: This paper is concerned with the moral concept of harm in the context of the Warsaw International Mechanism for Loss and Damage. This paper delineates between two concepts of wrongful harm: interactional versus architectural. It then examines these options with an eye toward developing a satisfactory normative approach for policy. While the interactional view of wrongful harm supports powerful arguments about moral responsibility, it has some clear limitations. This paper makes a case for the architectural view by underlining that it is not only compatible with the features of the Paris Agreement but also supports a distinctive conception of justice.